Isolation and Molecular Identification of Vahlkampfiidae and Vermamoeba Vermiformis from Fresh Vegetables: A Neglected Source of Infections - Marziye Fatemi; Maryam Niyyati; Seyed Ahmad Karamati; Hamed Mirjalali (Iranian Journal of Parasitology, 2024)
Background: Naegleria spp., Tetramitus spp., and Vermamoeba vermiformis are potential pathogenic free-living amoebae (FLA) causing diseases such as keratitis, meningoencephalitis, and lung infections. We aimed to investigate the presence of Vahlkampfiidae and V. vermiformis in raw vegetables commonly consumed in Iran.